2020
DOI: 10.1016/j.ebiom.2019.102613
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal hypoferremia in low birthweight and preterm babies: A prospective cohort study in hospital-delivered Gambian neonates

Abstract: Background: Neonates, particularly those born preterm (PTB) and with low birthweight (LBW), are especially susceptible to bacterial and fungal infections that cause an estimated 225,000 deaths annually. Iron is a vital nutrient for the most common organisms causing septicaemia. Full-term babies elicit an immediate postnatal hypoferremia assumed to have evolved as an innate defence. We tested whether PTB and LBW babies are capable of the same response. Methods: We conducted an observational study of 152 babies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…This study reconfirms our previous observation of a rapid and acute hypoferremia in the first day of life 16,17 with serum iron dropping from 23 to7 µmol/L and TSAT falling from 50 to 14%. This may have evolved as an arm of innate immunity designed to protect from neonatal septicemia, a common cause of neonatal death.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study reconfirms our previous observation of a rapid and acute hypoferremia in the first day of life 16,17 with serum iron dropping from 23 to7 µmol/L and TSAT falling from 50 to 14%. This may have evolved as an arm of innate immunity designed to protect from neonatal septicemia, a common cause of neonatal death.…”
Section: Discussionsupporting
confidence: 91%
“…IL-6 also activates the JAK-STAT pathway, leading to the induction of hepcidin synthesis 15 . In previous studies, we 16,17 and others [18][19][20][21] have demonstrated a rapid and profound hypoferremia occurring within the first few hours after delivery. This is assumed to have evolved as a defence against early-onset neonatal sepsis (EONS) and remains robust in premature and low-birthweight babies 17 .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In our individuals, serum folate concentrations were generally high, with a mean value of 37.71 nmol/l. Beside the previously known factors (prematurity, preeclampsia) (36,37), the results showed that folate de ciency (< 32.5 nmol/l) before 18 weeks gestation was an independent risk factor for LBW in eastern Chinese pregnant women. This is more accurate than studying the relationship between folic acid supplementation and LBW.…”
Section: Discussionmentioning
confidence: 68%
“…We intend to enrol 100 infants in the trial, which will be sufficient to have 80% probability that, if the true increase in geometric mean serum iron concentration in the iron group increases by 70% or more relative to the control group, the 95% confidence interval for the ratio would exclude zero (with the additional assumptions that the variance of log e serum iron concentration [in µmol/L] is 0.76 for each group 13 ; 10% of infants in the iron group stop taking iron supplements in the course of the intervention period; and the percentage of infants in the control group who stop taking placebo supplements is negligible) ( Figure 3 ). In absolute terms, an increase by 70% corresponds to a change of geometric mean serum iron concentration of 3.0µmol/L, assuming that this concentration is 4.3µmol/L in the placebo group (as observed at Day 0 in Armitage et al 2019 1 ), so that it will have increased 7.3µmol/L in the iron group.…”
Section: Protocolmentioning
confidence: 99%